2016
DOI: 10.1039/c6cc04938a
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a VHL and HIF1α interaction inhibitor with in vivo angiogenic activity via structure-based virtual screening

Abstract: We describe herein compound 1, which is similar to many known natural products, as an inhibitor of the VHL-HIF1α interaction via structure-based virtual screening. Compound 1 disrupts VHL-mediated HIF1α degradation, leading to significantly increased VEGF expression. To our knowledge, compound 1 is a member of only the second class of small molecule inhibitors of the VHL-HIF1α interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Among the different types of drug design methods, PBDD has the highest reliability [9]. A search for potential enzyme inhibitors for new drug development or therapeutic drug repurposing has been carried out with the aid of these methods, such as the study by Wu et al [10] and Yang et al [11], who identified mitoxantrone 1 as a new ATP-competitive inhibitor of NEDD8-activating enzyme (NAE) by virtual screening and an inhibitor of the VHL-HIF1α interaction via structure based virtual screening, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different types of drug design methods, PBDD has the highest reliability [9]. A search for potential enzyme inhibitors for new drug development or therapeutic drug repurposing has been carried out with the aid of these methods, such as the study by Wu et al [10] and Yang et al [11], who identified mitoxantrone 1 as a new ATP-competitive inhibitor of NEDD8-activating enzyme (NAE) by virtual screening and an inhibitor of the VHL-HIF1α interaction via structure based virtual screening, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products have long been regarded as a rich source of structural motifs for drug discovery 19. , 20.…”
Section: Introductionmentioning
confidence: 99%
“…HIF1α is a protein composed of 352 amino acid residues (Semenza 2007). Considering its important role in many cancers, developing a high efficient HIF1α inhibitors is becomes a priority (Yang et al 2016). After years of effort, many kinds of inhibitors were designed and tested.…”
Section: Introductionmentioning
confidence: 99%